Genetic diversity and population structure of Leptosphaeria maculans isolates in Western Canada. (20th November 2021) - Chen, Qilin; Peng, Gary; Kutcher, Randy; Yu, Fengqun
Abstract: Leptosphaeria maculans is a serious concern for canola production worldwide. For effective disease management, knowledge of the pathogen's genetic variability and population structure is a prerequisite. In this study, whole-genome sequencing was performed for 162 of 1590 L. maculans isolates collected in the years 2007–2008 and 2012–2014 in Western Canada. DNA variants in genome-wide and specific regions including avirulence ( Avr ) genes were characterized. A total of 31, 870 high-quality polymorphic DNA variants were used to study L. maculans genetic diversity and population structure. Cluster analysis showed that 150 isolates were clustered into 2 main groups and 4 subgroups by DNA variants located in either Avr or small secreted protein-encoding genes and into 2 main groups and 6 subgroups by genome-wide variants. The analysis of nucleotide diversity and differentiation also confirmed genetic variation within a population and among populations. Principal component analysis with genome-wide variants showed that the isolates collected in 2012–2014 were more genetically diverse than those collected in 2007–2008. Population structure analysis discovered three distinct sub-populations. Although isolates from Saskatchewan and Alberta were of similar genetic composition, Manitoba isolates were highly diverse. Genome-wide association study detected DNA variants in genes AvrLm4-7, Lema_T86300, and Lema_T86310 associated with the years of collection.